E-Learning Models: The Effectiveness of the Cloud-Based E-Learning Model over the Traditional E-Learning Model - Alajmi, Qasim; Sadiq, Ali Safa; Adzhar, Kamaludin; Al-Sharafi, Mohammed A. (IEEE, 2017)
This paper sought to understand the effectiveness of the traditional and cloud-based e-learning model. The growth of internet has been a game changer in the education sector. The internet has made it easy to for learners and educators to share information interactively, which is vital in enhancing education. Nonetheless, the storage of the content of learning has led to the adoption of cloud computing in the education sector in general and in higher education in particular. The adoption of cloud computing is in line with the objective of saving resources/saving costs and improving the interaction between students and the educators. Cloud-based learning has been slowly gaining popularity, with researchers arguing that it has the potential of replacing/improving the traditional e-learning model. It is worth noting safety (privacy and security) of information and data remains a huge priority for individuals who want to the e-learning model the best learning model for individuals learning from home and for education providers as well. The study utilizes a quantitative technique, where participants were drawn from two institutions. The respondents answered and presented a questionnaire for evaluation. Based on the results of the study, it was clear that the cloud-based e-learning model could effectively address the problems related to the traditional e-learning model. There is a need to improve the safety of the information contained in the e-learning platforms.